Artificial intelligence based serious game design and control using brain waves - Juspi, Enrique (Nanyang Technological University, 2023)
Exploring the fusion of Artificial Intelligence (AI) with Serious Game design, this study investigates the potential of brainwave data for advancing Brain-Computer Interface (BCI) interaction. By integrating machine learning into BCI, it aims to improve and smoothen the gaming experiences. Through data recorded from the brain waves and BCI response time, game programmers/designers are able to adjust gameplay balance. As technology gets better, EEG games are leading the way in combining brain science and gaming. They offer a future where our minds can create amazing and interactive gaming experiences, providing both fun and therapeutic benefits. However, challenges such as signal precision and data privacy are still a consideration. In this project, the Emotiv EPOC EEG headset will be used as the input device for the game, “Counter Spell”.